Financing social enterprises through cash waqf: An Innovation of business model - Nur Fauziah, Najim; Mohd. Zain, Nor Razinah; Mohd Noor, Azman; Zakariyah, Habeebullah (2020)
This research explores potentials of cash Waqf in generating capital revenue in carrying out social-based investment through social enterprises. Looking closely into two different concepts i.e. social enterprises and Waqf, this research appreciates the understanding on the modern business model of social enterprise and the innovative version of religious social finance i.e. cash Waqf. Depending on qualitative methodology and analytical review, the discussion of this research is developed. These approaches are considered suitable and pragmatic for the suggested business model of social enterprise. Here, an innovative business model with a combination of social enterprise operation and cash Waqf is introduced. It has the potential to stimulate further research to innovate religious social finance instruments to current and modern business models.